Pre-Service English Teachers’ Perception on the Use of Applications in Designing English Instructional Media - Al Na'im, Nadhrah; Rozal, Edi; Andriani, Reni; Mananghaya, Michael E (E-Link Journal, 2025)
As educational practices increasingly rely on technology, teacher education programs are under pressure to integrate digital tools, especially for Indonesian pre-service EFL teachers. Despite this growing emphasis, comprehensive studies addressing how these prospective teachers interpret and evaluate the use of digital applications for instructional media design are still scarce. Accordingly, the present study was designed to explore these perceptions through an analysis of attitudes, instructional implementation, and fundamental belief systems. This research adopted a survey-based quantitative design involving 44 sixth-semester students who had completed micro-teaching as part of their academic requirements. Conducted in December 2024 at the English Education Study Program of UIN Sulthan Thaha Saifuddin Jambi, the study collected data through a Google Forms instrument with 23 items organized into three thematic dimensions. Analysis of the responses produced an overall mean of 4.1, suggesting very favorable perceptions toward educational applications, notably for their contribution to active student participation, interactive learning processes, and effective teacher–student interaction. The study suggests that continuous professional training is necessary to equip future educators with the competencies required for effective integration of digital tools. These findings support the inclusion of structured digital literacy components in teacher education curricula.